Congeneric lantibiotics from ribosomal in vivo peptide synthesis with noncanonical amino acids - Oldach, Florian (2019)
Expanded repetoire: Synthetic amino acids translated into propeptides dramatically increase the chemical diversity of the two-component lantibiotic lichenicidin. This opens new routes towards novel and unique peptide antibiotic sequences, which could display features important for medical applications.